Pasternak i Majakowski. Historia znajomości - Zygmunt Zbyrowski (Studia Rossica Posnaniensia)
Both eminent Russian poets shared much, although they also differed considerably. Peers, they debuted almost simultaneously as Futurists, though their personal contacts began with a conflict within the Futuristic milieu. They were poets-urbanists, but Mayakovsky was captivated by urban civilization as well as ethical and social phenomena, while Pasternak was fascinated with municipal parks. Their acquaintanceship consisted of mutual attraction and recognition, especially for their early, pre-revolutionary works. After the revolution Mayakovsky attempted to draw Pasternak into his organizational initiatives and publication undertakings. Pasternak’s protests led to conflicts and a severance of ties. Despite the deterioration in their relations, Pasternak was deeply touched by Mayakovsky’s suicide.